Projected future changes in extreme climate indices affecting rice production in China using a multi-model ensemble of CMIP6 projections - Chen, Xinmin; Xiao, Dengpan; Qi, Yongqing; Shi, Zexu; Bai, Huizi; Lu, Yang; Zhang, Man; Pan, Peipei; Ren, Dandan; Yin, Xiaomeng; Li, Renjie (Frontiers in Plant Science, 2025)
Assessing and predicting the spatial-temporal characteristics of extreme climate events can effectively identify the impacts of climate change on crop production and propose targeted measures. This study systematically evaluates the intensity and spatiotemporal evolution of extreme climate events during critical phenological stages in China’s major rice-growing regions based on 11 extreme climate indices (ECIs). The future climate data were obtained from 18 Global Climate Models (GCMs) integrated in the Coupled Model Intercomparison Project phase 6 (CMIP6) with four shared socio-economic pathways (SSPs) to project the future changes of ECIs related rice production. The results indicate that the multi-model ensemble constructed via the Independence Weighted Mean method (IWM) significantly outperformed both the arithmetic mean method (AM) and individual GCMs in replicating observed trends of 11 ECIs during the historical period (1981–2014), with notable reductions in root mean square error (RMSE) for certain indices. The projections reveal that under the SSP585 scenario, the duration of extreme heat events (e.g., HD) in southern China will increase by 12–18 days by the 2080s compared to the historical period (1981–2014), representing the highest increase among all scenarios. The extreme drought events (e.g., D-Vgp) in northeastern China are projected to reach 14.8, 9.7, and 9.7 days by the 2040s, further rising to 14.3, 10.0, and 10.3 days by the 2080s. The extreme precipitation events are predominantly concentrated in southwestern and southern China, with consecutive wet days (CWD) showing limited increase within 3 days. The findings highlight that China’s rice cultivation will face intensified extreme climate challenges in the future, particularly extreme heat stress, necessitating urgent adaptive strategies to mitigate the adverse impacts of climate change on rice production.